2012
DOI: 10.1563/aaid-joi-d-10-00046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Guide Design and Surgeon's Experience on the Accuracy of Implant Placement

Abstract: AcknowledgementsI would like to thank Dr. Wook-Jin Seong and Dr. Heather Conrad for their help and support throughout this study.I would like to thank Scott Lunos for assistance with statistics and Lianshan Lin computing assistance.Also, I gratefully acknowledge Dr. James E. Hinrichs for advice and support throughout all aspects of my residency in Periodontology.I gratefully acknowledge the support of the American Academy of Implantology Research Foundation in Chicago, Il, for their grant of $10,000.ii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 21 publications
(31 reference statements)
3
21
0
2
Order By: Relevance
“…Multiple in-vitro studies found a statistically significant difference between the experienced and inexperienced surgeons for angular and horizontal error at the implant apex and platform. 13,14 The degree of bucco-lingual deviation in the expert surgeon group in our study was within the normal range of previous studies. The expert surgeon group in Cushen and Turkyilmaz 13 study performed with a horizontal angular deviation of 2.60 ± 1.25.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Multiple in-vitro studies found a statistically significant difference between the experienced and inexperienced surgeons for angular and horizontal error at the implant apex and platform. 13,14 The degree of bucco-lingual deviation in the expert surgeon group in our study was within the normal range of previous studies. The expert surgeon group in Cushen and Turkyilmaz 13 study performed with a horizontal angular deviation of 2.60 ± 1.25.…”
Section: Discussionsupporting
confidence: 82%
“…The authors anticipated that the magnitude of deviation in accuracy of implant angulation would be higher if novice surgeons operated in a real clinical setting. 14 The real clinical setting is a complex environment that might exert a cognitive load on novice learners, negatively affecting their performance.…”
Section: Introductionmentioning
confidence: 99%
“…The size and the location of the edentulous site were found to significantly affect the accuracy of implant placement via a tooth-supported SLA guide [18,31]. In this study, each dentist placed three implants at different sites of the model in which two were in a distal free-end situation.…”
Section: Discussionmentioning
confidence: 94%
“…They concluded that more experienced operators place implants more accurately. Hinckfuss et al [18] reported significantly less angulation error in the buccal-lingual direction for experienced operators utilizing tooth-supported surgical guides, yet no significant difference in positional errors was found between experienced and inexperienced operators. A similar result was reported by Fernandez-Gil et al in a model study using a tooth-supported guide [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation